2015
DOI: 10.1167/iovs.15-16967
|View full text |Cite
|
Sign up to set email alerts
|

Blink Rate and Incomplete Blinks in Six Different Controlled Hard-Copy and Electronic Reading Conditions

Abstract: PURPOSE. To evaluate spontaneous eye blink rate (SEBR) and percentage of incomplete blinks in different hard-copy and visual display terminal (VDT) reading conditions, compared with baseline conditions. METHODS.A sample of 50 participants (29 females, age range, 18-74 years) were recruited for this study. All participants had good ocular health and reported no symptoms of dry eye (OSDI score < 15). Face video recordings were captured while participants observed in silence a landscape picture at 2 m (baseline) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
98
1
4

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 107 publications
(109 citation statements)
references
References 34 publications
(48 reference statements)
6
98
1
4
Order By: Relevance
“…We found that reading a book reduced the blink rate more than reading text on an electronic device; this is in agreement with the work of Argilés et al23 They found that the blink rate was significantly lower when reading a book than text on an electronic device (9.7 inch tablet). Although the blink rate was higher when the electronic device was used, employment of an electronic device increased the incidence of incomplete blinks compared with hard copy reading condition 23…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…We found that reading a book reduced the blink rate more than reading text on an electronic device; this is in agreement with the work of Argilés et al23 They found that the blink rate was significantly lower when reading a book than text on an electronic device (9.7 inch tablet). Although the blink rate was higher when the electronic device was used, employment of an electronic device increased the incidence of incomplete blinks compared with hard copy reading condition 23…”
Section: Discussionsupporting
confidence: 93%
“…This is in agreement with the findings of previous studies; blink rates dropped significantly under different reading conditions 26. One possible explanation is that the attentional demand is higher during reading tasks, perhaps reducing the blink rate 23. Alternatively, use of the down-gaze position may be preferred during reading, which could in turn reduce the blink rate 3…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…One of the most prevalent problems associated with CVS is dry eye [4]. Researchers have reported that ocular discomfort, specifically dry eye symptoms, may be associated with an increase of incomplete blinks (that is, the eye is not completely closed in the downward process of a blink) when electronic displays are used [5].…”
Section: Introductionmentioning
confidence: 99%